Glomerular Biomechanical Stress and Lipid Mediators during Cellular Changes Leading to Chronic Kidney Disease - Mukut Sharma; Vikas Singh; Ram Sharma; Arnav Koul; Ellen T. McCarthy; Virginia J. Savin; Trupti Joshi; Tarak Srivastava (Biomedicines, 2022)
Hyperfiltration is an important underlying cause of glomerular dysfunction associated with several systemic and intrinsic glomerular conditions leading to chronic kidney disease (CKD). These include obesity, diabetes, hypertension, focal segmental glomerulosclerosis (FSGS), congenital abnormalities and reduced renal mass (low nephron number). Hyperfiltration-associated biomechanical forces directly impact the cell membrane, generating tensile and fluid flow shear stresses in multiple segments of the nephron. Ongoing research suggests these biomechanical forces as the initial mediators of hyperfiltration-induced deterioration of podocyte structure and function leading to their detachment and irreplaceable loss from the glomerular filtration barrier. Membrane lipid-derived polyunsaturated fatty acids (PUFA) and their metabolites are potent transducers of biomechanical stress from the cell surface to intracellular compartments. Omega-6 and ω-3 long-chain PUFA from membrane phospholipids generate many versatile and autacoid oxylipins that modulate pro-inflammatory as well as anti-inflammatory autocrine and paracrine signaling. We advance the idea that lipid signaling molecules, related enzymes, metabolites and receptors are not just mediators of cellular stress but also potential targets for developing novel interventions. With the growing emphasis on lifestyle changes for wellness, dietary fatty acids are potential adjunct-therapeutics to minimize/treat hyperfiltration-induced progressive glomerular damage and CKD.